Clonidine as an adjuvant for propranolol enhances its effect on infiltrative cutaneous analgesia in rats. (11th March 2016) - Hung, Ching-Hsia; Chiu, Chong-Chi; Liu, Kuo-Sheng; Wang, Jhi-Joung; Chen, Yu-Wen
Highlights: Propranolol and bupivacaine produces dose-dependently infiltrative anesthetic effects. Subcutaneous propranolol is less potent than bupivacaine as an infiltrative anesthetic. Duration caused by propranolol is comparable to that caused by bupivacaine. Clonidine increases the depth and duration of action by propranolol and bupivacaine. Abstract: Clonidine prolongs duration of analgesia when used as an adjunct to local anesthetics for infiltrative cutaneous analgesia, and propranolol produces local anesthesia. The purpose of the experiment was to evaluate clonidine as an adjuvant for propranolol on the quality and duration of cutaneous analgesia. A rat model of cutaneous trunci muscle reflex (CTMR) in response to local skin pinprick was employed to evaluate the cutaneous analgesic effect of propranolol combined with clonidine. The long-lasting local anesthetic bupivacaine was used as control. Cutaneous analgesia elicited by propranolol and bupivacaine was dose-dependent, and both propranolol (9.0 μmol) and bupivacaine (1.8 μmol) produced 100% nociceptive blockade. On an 50% effective dose (ED50 ) basis, the relative potency was bupivacaine [0.48 (0.42–0.55) μmol] greater than propranolol [2.27 (1.98–2.54) μmol] ( p  < 0.01). Subcutaneous saline and clonidine (0.12 μmol) did not produce cutaneous analgesia. The mixture of an ineffective-dose clonidine (0.12 μmol) and a drug (propranolol or bupivacaine) at ED50 or ED95 increased the potency and extended the duration at producing cutaneous analgesia. The resulting data demonstrated that propranolol is less potent than bupivacaine as an infiltrative anesthetic. Clonidine as an adjuvant for propranolol or bupivacaine has a significant peripheral action in increasing the depth and duration of action on infiltrative cutaneous analgesia.